Pertanggungjawaban Pidana Pengurus Yayasan dalam Penggelapan Kekayaan Yayasan Pendidikan - Rusito; Doni Adi Supriyo (Faculty of Law, Universitas Wijayakusuma Purwokerto, 2024)
This study aims to describe the Criminal Liability of Foundation Administrators in Misuse of Educational Foundation Assets. The method used in this study is normative juridical, namely research with data sources based on Laws, decisions, and other legal materials related to this scientific work with a Criminal Law perspective. Criminal acts of embezzlement in office without us realizing have occurred a lot and are difficult to identify because the perpetrators are still in the same scope as the institution, organization or company. The results of this study indicate that the defendant can be sentenced by the judge under Article 364 of the Criminal Code in conjunction with Article 64 of the Criminal Code so that the defendant is sentenced to 1 year in prison and is required to return the proceeds of the crime. In fact, Indonesia has special regulations governing Foundations along with criminal penalties for those who violate the legal provisions in Law No. of 2004 concerning amendments to Law No. of 2001 concerning Foundations. This is because there are certain criteria, namely the perpetrator as a core organ of the Foundation (Supervisor, Manager, Supervisor) so that someone who violates the provisions can be subject to articles in accordance with the Foundation Law. Keywords: Criminal Act, Embezzlement, Educational Foundation